Noninvasive positive pressure ventilation : principles and applications - Hill, Nicholas (Futura, 2001)
Noninvasive Positive Pressure Ventilation offers practical, evidence-based advice from experienced authors on the selection of appropriate patients, equipment and techniques used in the initiation of noninvasive positive pressure ventilation (NPPV). It discusses how to anticipate and resolve possible problem scenarios, and how to implement and monitor NPPV programs both in hospitals and in the patient\'s home. Defined as ventilatory assistance given without the need for an invasive airway, NPPV is often preferred over invasive mechanical ventilation because it is more convenient to use, more comfortable for the patient, and avoids complications of invasive mechanical ventilation including upper airway trauma, nosocomial pneumonias, sinusitis and sepsis. However, recipients of NPPV must be carefully selected and considerable skill and experience are necessary for successful implementation. This book aims to provide readers with knowledge that will contribute to that success. Noninvasive Positive Pressure Ventilation will inform pulmonary internists and pediatricians, pulmonary physiatrists and physicians, nurses and respiratory therapists who are involved in the management of patients with respiratory failure, critical care physicians and nurses, and trainees and students who have an interest in mechanical ventilation.
Keywords: ventilace umělá s přerušovaným přetlakem; Intermittent Positive-Pressure Ventilation; Respiratory Therapy; pneumologie a ftizeologie; dechová terapie